2014
DOI: 10.1021/jp503769d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Investigations on Single-Atom Catalysis: Ir1/FeOx for CO Oxidation

Abstract: Through periodic density functional theory (DFT) calculations we have investigated the catalytic mechanism of CO oxidation on an Ir1/FeO x single-atom catalyst (SAC). The rate-determining step in the catalytic cycle of CO oxidation is shown to be the formation of the second CO2 between the adsorbed CO on the surface of Ir1/FeO x and the dissociated O atom from gas phase. Comparing with Pt1/FeO x catalyst, the reaction activation barrier for CO oxidation is higher by 0.62 eV and the adsorption energy for CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
157
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(168 citation statements)
references
References 45 publications
10
157
0
Order By: Relevance
“…[104] An independent study later found that Pd 1 /FeO x should be more active. [108] Thep erformance of many of the systems identified has yet to be confirmed experimentally, and in some cases the synthesis has still not been reported. [108] Thep erformance of many of the systems identified has yet to be confirmed experimentally, and in some cases the synthesis has still not been reported.…”
Section: Methodsmentioning
confidence: 99%
“…[104] An independent study later found that Pd 1 /FeO x should be more active. [108] Thep erformance of many of the systems identified has yet to be confirmed experimentally, and in some cases the synthesis has still not been reported. [108] Thep erformance of many of the systems identified has yet to be confirmed experimentally, and in some cases the synthesis has still not been reported.…”
Section: Methodsmentioning
confidence: 99%
“…Activity for various reactions has so far been demonstrated for metals including Ir [483], Au [484], Pt [485][486][487][488], and this has motivated theoretical studies aimed at understanding how it is that a single atom can function as a catalyst [489]. Unfortunately, the complexity of the "FeO x " support, usually a reduced α-Fe 2 O 3 , means that the termination of the oxide is not known.…”
Section: Metalsmentioning
confidence: 99%
“…1016 Pt 1 /FeO x was firstly synthesized and utilized as a single atom catalyst for CO oxidation with extremely high activity and stability. 17 Recently, a single Ni atom was successfully doped at lattice defects of graphene and showed exceptional activity for electrochemical hydrogen production 12 due to electronic interactions 18 between the metal and graphene.…”
Section: Introductionmentioning
confidence: 99%